A roma fiatalok esélyei és az iskolarendszer egyenlőtlensége - Gábor Kertesi; Gábor Kézdi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2016)
– Using unique data from Hungary we analyze the educational attainment of a cohort of Hungarian Roma and non-Roma students. This cohort started high school in 2006. High school dropout rate is 10 percent among non-Roma, whereas nearly 50 percent among Roma students. 75 percent of the non-Roma students take a final maturity exam, and the college attendance rate is 31 percent among them. The corresponding figures for Roma are 24 percent and 4 percent, respectively. The ethnic difference in high school attainment and college attendance are strongly related to the skills gap emerged before high school. The ethnic test score gap measured by the end of 8th grade is nearly entirely explained by social differences in income, wealth and parental education, while ethnic factors do not play an important role. Two major mediating mechanisms can be identified: first, the home environment of Roma children is less favorable for their cognitive development; second, Roma children face a lower quality educational environment. Comparing children with similar home environments from the same school and class, we find that the ethnic gap in test scores is insignificant. Ethnic differences in the home environment are explained by social differences, and ethnicity seems to play no additional role. While their disadvantage in accessing high-quality education is also strongly related to social differences, Roma students seem to face additional disadvantages as subjects of ethnic segregation. The majority of Roma students are educated in classrooms in which the sheer quantity of unresolved pedagogical problems makes it very difficult for teachers to teach well. The raw ethnic difference in the likelihood of studying in classes in which over half of the classmates can be considered functionally illiterate, is 40 percentage points. Residential inequalities and selection by social disadvantage are responsible for the bulk of this selection; however, ethnic exclusion mechanisms are responsible for the rest.
Keywords: I20; J15; 330; Roma minority; test score gap; school segregation; high school completion; college attendance